Compositional and isotopic heterogeneities in the Neo-Tethyan upper mantle recorded by coexisting Al-rich and Cr-rich chromitites in the Purang peridotite massif, SW Tibet (China). (15th June 2018) - Xiong, Fahui; Yang, Jingsui; Xu, Xiangzhen; Kapsiotis, Argyrios; Hao, Xiaolin; Liu, Zhao
Graphical abstract: Highlights: High-Cr (Cr# Sp : 62.55–79.57) and high-Al (Cr# Sp : 47.60–57.56) podiform chromitites coexist in the Purang peridotite massif. They show enrichment in IPGE over PPGE and their PGM assemblages are dominated by laurite. γ Os values are generally negative indicating a sub-chondritic mantle source for the parental melts of chromitites. The Purang chromitites originated from geochemically distinct magma inputs derived from melting of different sections of a mantle wedge above a SSZ. Abstract: The Purang harzburgite massif in SW Tibet (China) hosts abundant chrome ore deposits. Ores consist of 20 to >95% modal chromian spinel (Cr-spinel) with mylonitic fabric in imbricate shaped pods. The composition of Cr-spinel in these ores ranges from Al-rich [Cr# Sp or Cr/(Cr + Al) × 100 = 47.60–57.56] to Cr-rich (Cr# Sp : 62.55–79.57). Bulk platinum-group element (PGE) contents of chromitites are also highly variable ranging from 17.5 ppb to ∼2.5 ppm. Both metallurgical and refractory chromitites show a general enrichment in the IPGE (Os, Ir and Ru) with respect to the PPGE (Rh, Pt and Pd), resulting mostly in right-sloping primitive mantle (PM)-normalized PGE profiles. The platinum-group mineral (PGM) assemblages of both chromitite types are dominated by heterogeneously distributed, euhedral Os-bearing laurite inclusions in Cr-spinel. The Purang chromitites have quite inhomogeneous 187 Os/ 188 Os ratios (0.12289–0.13194) that are within the range of those reported for mantle-hosted chromitites from other peridotite massifs. Geochemical calculations demonstrate that the parental melts of high-Cr chromitites were boninitic, whereas those of high-Al chromitites had an arc-type tholeiitic affinity. Chromite crystallization was most likely stimulated by changes in magma compositions due to melt-peridotite interaction, leading to the establishment of a heterogeneous physicochemical environment during the early crystallization of the PGM. The highly variable PGE contents, inhomogeneous Os-isotopic compositions and varying Cr# Sp ratios of these chromitites imply a polygenetic origin for them from spatially distinct melt inputs. The generally low γ Os values (<1) of chromitites indicate that their parental melts originated within different sections of a heterogeneously depleted mantle source region. These melts were most likely produced in the mantle wedge above a downgoing lithospheric slab.